Pengaruh Current Ratio, Debt to Equity Ratio dan Return on Asset terhadap Harga Saham pada Perusahaan Manufaktur Sektor Property dan Real Estate yang Terdaftar di BEI - Juwita Manalu; Rikananda Sibarani; Benny Rojeston Marnaek Nainggolan (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of the variable current ratio, debt to equity ratio and ROA on capital structure. This research method is descriptive quantitative. Data collection techniques were carried out through documentation techniques and data analysis using multiple linear analysis using the F test and t test. The results showed, a) the current ratio variable has a value of tcount<ttable, namely -0.988<1.66105 with a significant level of 0.326> 0.05; b) the variable debt to equity ratio has a value of tcount<ttable, namely -3.217> 1.66105o with a significant level of 0.002<0.05; c) the ROA variable has a tcount<ttable value of 5.112>1.66105o with a significant level of 0.000<0.05. In conclusion, partially the current ratio has no significant effect on capital structure, the debt to equity ratio has a significant negative effect on capital structure and ROA has a significant positive effect on capital structure. Simultaneously showing the current ratio, debt to equity ratio and ROA affect the capital structure. Keywords: Current Ratio, Debt to Equity Ratio, ROA, Capital Structure